Representations of Structural Deviation In The Poetry of Al-Hutai’a - Askar, Huda Gazy (Dzil Majaz: Journal of Arabic Literature, 2024)
Al-Hutai'a's poetry is considered one of the most significant examples of ancient Arabic poetry, reflecting artistic development in poetic structure and rhetorical techniques. Al-Hutai'a's poetry manifests various uses of structural deviation, which involves altering the traditional syntactic structure of a sentence to achieve specific aesthetic or semantic purposes. This study aims to analyze and interpret the representations of structural deviation in Al-Hutai'a's poetry, and to understand how this technique has contributed to adding depth and new meanings to poetic texts. The descriptive method is one of the research approaches that aims to describe Al-Hutai'a's poetry through the representations of structural deviation as they are, without intervention or attempt to change them. The researcher attempted to apply this method by systematically collecting and analyzing data to determine and interpret the relationships between the different variables of the research topic. The study of structural deviation in the poetry of Al-Hutai'a represents a valuable contribution to understanding the development of rhetorical techniques in ancient Arabic poetry. The research reveals the importance of structural deviation as a rhetorical tool that enhances the beauty of the text and enriches its meanings, highlighting Al-Hutai'a's skill in using this technique to achieve his poetic aims. This study is a significant addition to Arabic literature and rhetorical studies, as it sheds light on an important aspect of Al-Hutai'a's creativity and his influence on Arabic poetry